2017
DOI: 10.1080/09692290.2017.1403358
|View full text |Cite
|
Sign up to set email alerts
|

The origins of national housing finance systems: a comparative investigation into historical variations in mortgage finance regimes

Abstract: This paper advances the first historically informed typology of housing finance systems. Using a novel collection of historical mortgage-market data, we identify four different ‘ideal type’ systems, which developed in mature economies when organised housing finance institutions began to emerge with the advance of industrialism and urbanism throughout the long nineteenth century: informal person-to-person lending, and state lending as solutions outside specialised banking circuits; and deposit-based and bond-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…These insights have also penetrated CPE, particularly in the work of Gerber and Schelkle (2013) and Ansell (2014). Recent works in CPE have also demonstrated that house price inflation is closely connected to the institutions that shape income growth and mortgage markets (see Johnston and Regan 2017;Schwartz and Seabrooke 2008), and that housing is central to the politics of social policy preference formation, particularly where finance is concerned (Blackwell and Kohl 2018;Bohle 2014;Kohl 2018). Within the housing literature, there is a parallel discussion taking place: the state of the art suggests that pro-homeownership public policy regimes facilitate financialised approaches to the welfare state (Lennartz and Ronald 2017).…”
mentioning
confidence: 98%
“…These insights have also penetrated CPE, particularly in the work of Gerber and Schelkle (2013) and Ansell (2014). Recent works in CPE have also demonstrated that house price inflation is closely connected to the institutions that shape income growth and mortgage markets (see Johnston and Regan 2017;Schwartz and Seabrooke 2008), and that housing is central to the politics of social policy preference formation, particularly where finance is concerned (Blackwell and Kohl 2018;Bohle 2014;Kohl 2018). Within the housing literature, there is a parallel discussion taking place: the state of the art suggests that pro-homeownership public policy regimes facilitate financialised approaches to the welfare state (Lennartz and Ronald 2017).…”
mentioning
confidence: 98%
“…62 If nonregistered interpersonal mortgages are included, an estimated 90 percent of mortgages were interpersonal around 1900 in Canadian cities, 63 and as many as one-third of mortgages in post-WWII Switzerland. 64 When mortgage banks emerged in the nineteenth century-as specialized bond-based mortgage banks or building societies or as general savings banks 65 -their market often constituted only a minority. In other words, the bank-centered measures downplay the increases of mortgages that happened particularly during the earlier nonbanking periods of homeownership increases.…”
Section: Discussionmentioning
confidence: 99%
“…These point to at least three important shifts in housing finance and house price dynamics, which need to be explained by macroeconomic and political economy theories. Firstly, Blackwell and Kohl (2018) and Kohl (2018) give an overview of the history of mortgage credit institutions. These differ in important ways from the banks that deal with businesses.…”
Section: Economic and Financial Historymentioning
confidence: 99%
“…In contrast, financial crises or house prices cycles do not feature. Blackwell and Kohl (2018) provide a history of housing finance. They offer a classification based on the distinction a deposit-based bank system, a mortgage bond-based bank system, state-based and a peer-based lending system.…”
Section: Comparative Political Economy and The Financialisation Debatesmentioning
confidence: 99%